THE EFFECTIVENESS OF USING THE MIND MAPPING LEARNING METHOD TO IMPROVE THE ABILITY TO WRITE NARRATIVE ESSAYS IN SUKAHATI PUBLIC ELEMENTARY SCHOOL STUDENTS - Sopian, Sopian (Jurnal Multidisiplin Sahombu, 2023)
The purpose of this research is to investigate whether or not primary school students are better able to compose narrative essays after participating in a mind mapping learning activity. The approach that was taken was one that was considered to be quasi-experimental, and it was implemented with three students from the sixth grade at Sukahati Indramayu Public Elementary School. Observation and careful documentation are the two main components of the data collection process. After undergoing a number of treatments, the subject's score improved, as demonstrated by the findings. After receiving treatment, the subjects saw a rise in their scores, going from an average of 160.75 before treatment to 232.75 after treatment. It is possible to draw the following conclusion as a result: the application of the mind mapping method has a beneficial effect on the capacity of elementary school children to compose narrative essays.